Intercultural Components in the Multimodal Structure of a Language Learning Website - Alejandro Fernández Benavides (Universidad Nacional de Colombia, 2019)
The emergence of language learning websites has generated changes in intercultural communicative practices. Particularly, these sites use a wide variety of modes of communication (visual, linguistic, spatial) which allow the presence of intercultural elements. This interpretative case study analyzes the semiotic structure of one lesson of the language learning website Livemocha in order to unveil the presence of intercultural elements in it. Data were analyzed following a method for multimodal analysis and Byram's model of intercultural communicative competence. Findings suggest the essentialist view of culture on Livemocha, based on festivals and food, and the potential promotion of some of Byram's intercultural skills.